The thyroid hormone enhances mouse embryonic fibroblasts reprogramming to pluripotent stem cells: role of the nuclear receptor corepressor 1 - Contreras-Jurado, Constanza; Montero-Pedrazuela, Ana; Pérez, Raúl F.; Alemany, Susana; Fraga, Mario F.; Aranda, Ana (Frontiers in Endocrinology, 2023)
Introduction Pluripotent stem cells can be generated from somatic cells by the Yamanaka factors Oct4, Sox2, Klf4 and c-Myc. Methods Mouse embryonic fibroblasts (MEFs) were transduced with the Yamanaka factors and generation of induced pluripotent stem cells (iPSCs) was assessed by formation of alkaline phosphatase positive colonies, pluripotency gene expression and embryod bodies formation. Results The thyroid hormone triiodothyronine (T3) enhances MEFs reprogramming. T3-induced iPSCs resemble embryonic stem cells in terms of the expression profile and DNA methylation pattern of pluripotency genes, and of their potential for embryod body formation and differentiation into the three major germ layers. T3 induces reprogramming even though it increases expression of the cyclin kinase inhibitors p21 and p27, which are known to oppose acquisition of pluripotency. The actions of T3 on reprogramming are mainly mediated by the thyroid hormone receptor beta and T3 can enhance iPSC generation in the absence of c-Myc. The hormone cannot replace Oct4 on reprogramming, but in the presence of T3 is possible to obtain iPSCs, although with low efficiency, without exogenous Klf4. Furthermore, depletion of the corepressor NCoR (or Nuclear Receptor Corepressor 1) reduces MEFs reprogramming in the absence of the hormone and strongly decreases iPSC generation by T3 and also by 9cis-retinoic acid, a well-known inducer of reprogramming. NCoR depletion also markedly antagonizes induction of pluripotency gene expression by both ligands. Conclusions Inclusion of T3 on reprogramming strategies has a potential use in enhancing the generation of functional iPSCs for studies of cell plasticity, disease and regenerative medicine.